Exploring the Complexities of Teacher Talk in English Language Learning: A Discourse Analysis - Amanah, Ainun; Hidayat, Didin Nuruddin; Husna, Nida; Hartono, Rodi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the complexities of teacher talk in English language learning through a discourse analysis of classroom interactions in a non-formal educational setting. The school provides a learning environment that caters to diverse groups of students, with a focus on developing their English communication skills. Three English teachers participated in the study. Classroom interactions were recorded and analyzed over two weeks using discourse analysis. Findings reveal that classroom interaction is shaped significantly by how teachers use language to facilitate learning. Teachers often face challenges in consistently using English, stemming from their limited proficiency and concerns about students' ability to comprehend. The study identifies key patterns of teacher talk, including questioning, giving instructions, lecturing, and using expressions to support student engagement and comprehension. These patterns are shown to impact student understanding and participation, particularly in contexts where English is not the primary language. Through discourse analysis, the study sheds light on how teacher talk functions within instructional conversations and highlights its influence on students' cognitive and communicative development in English language classrooms. Overall, the study shows that the way teachers talk in class affects how students learn and interact, especially in settings where English is not their first language. It also suggests that teacher training should pay more attention to classroom talk and how it can support language development.